Campo Grande stylo and elephant grass mixed silages treated with microbial inoculant - Ribeiro, Karina Guimarães; Souza, Igor Alexandre de; Rigueira, João Paulo Sampaio; Cezário, Andréia Santos; Valadares Filho, Sebastião de Campos; Pereira, Odilon Gomes (Semina: Ciências Agrárias, 2020)
Tropical grass has some advantages for ensilage, such as high annual production of dry matter per unit area, perennity, low loss risk, and higher harvest flexibility. We aimed with this study to assess the chemical composition, microbial population, fermentation characteristics, and effluent production of stylo (Stylosanthes capitata Ã— S. macrocephala cv. Campo Grande) silages with increasing proportions (0, 25, 50, 75, and 100%) of elephant grass (Pennisetum purpureum Schum. cv. Cameroon), with or without microbial inoculant. We used a 5Ã—2 factorial scheme in a completely randomized design, with three replicates. There was an effect of interaction between proportions of elephant grass and microbial inoculant on yeast population, butyric acid and ammonia-nitrogen content, and effluent loss. The proportions of elephant grass affected the chemical composition, lactic acid bacteria and mold populations, pH, and lactic and propionic acid contents. Dry matter, acid detergent insoluble nitrogen, and lactic acid contents and the pH values were negatively affected by microbial inoculant. We conclude that stylo provides silage with better chemical composition and lower effluent production, although with a higher mold and yeast population, than elephant grass. The microbial inoculant does not improve the chemical and fermentative characteristics of silages, except for the reduction of butyric acid. We recommend uninoculated stylo silage with up to 75% of elephant grass.